Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Review - Page 330: 70



Work Step by Step

Using $(a+b+c)^2=a^2+b^2+c^2+2ab+2ac+2bc$ or the square of a multinomial, then, \begin{array}{l} (m^2+m-2)^2 \\= (m^2)^2+(m)^2+(-2)^2+2(m^2)(m)+2(m^2)(-2)+2(m)(-2) \\= m^4+m^2+4+2m^3-4m^2-4m \\= m^4+2m^3+(m^2-4m^2)-4m+4 \\= m^4+2m^3-3m^2-4m+4 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.